Patria, iustitia et pax - ŁASZKIEWICZ, Hubert (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2013)
Pursuit of justice, peace and effi cacy is a universally declared aspiration in social life. However, the meaning of such concepts as the homeland, justice and social peace differs signifi cantly between individuals and social groups. Thus effective social action cannot refer merely to the intellectual rightness, but it should draw on the already existing solutions, which, however imperfect they are, express the intention to introduce the ideals of social peace (Pax), justice (Iustitia), and the feeling of belonging to a community (Patria) into both interpersonal relations as such and the relations among social groups.